Comparative evaluation of the Roche Cobas IDA and Enterotube II systems for identifying members of the family Enterobacteriaceae. - Holmes, B (1989)
Two Hoffmann-La Roche products were evaluated in parallel for their ability to identify 321 strains of the family Enterobacteriaceae. The first product was the well-established Enterotube II, which correctly identified 90% of the isolates after 24 h of incubation. The second was the ID-E rotor, originally designed for use in the Cobas Bact but here used in the new Cobas IDA system. The Cobas IDA, used with the full data base held in a microcomputer supplied with the product, identified 87% of strains after 4 h of incubation.